(untitled) (Impetus, 2021)
Programs to encourage the practice of physical exercise are increasingly spread around the world. It is known its importance for the maintenance and prevention of diseases and improvements in the quality of life associated with a healthy diet, even so, it is observed in studies, a high incidence of sedentary lifestyle in the population, especially in adolescents. A program of orientation of physical exercise and food consumption was implanted with the students of the Technical Courses Integrated to the High School of the IFSC / Campus Canoinhas and the objective of this research was to verify the impact of it. All students of Integrated High School (n=70) participated in this study, they received lectures, activities and interventions focused on knowledge about food and physical exercise. At the end they answered a questionnaire with ten questions. The results were positive, although only 16 (22,8%) made changes in their habits because of the interventions, but the majority (95,7%) considered that the interventions and acquired knowledge were important to reflect on their habits. New studies are needed to see which factors interfere in the attitude to adopt an active and healthy posture with the aim of improving the quality of life.